Anthropogenic Factors and Environmental Degradation in Indonesia (Empirical studies using the STIRPAT Model) - Diartho, Herman Cahyo; Fardian, M. Iqbal (Technium Social Sciences Journal, 2022)
The decrease in the quality of the environment is one of the key problems currently facing human society, especially if the decrease in environmental capacity to serve human needs is considered to be a factor in the emergence of global warming phonemes. In addition, all human actions are deemed responsible for the decline in environmental degradation. The aim of the paper is to see how, as formulated by the classical STIRPAT model, human activity in Indonesia are considered to be driving factors for the deterioration of environmental quality, particularly population, economic, and technology. The authors used the Extended STIRPAT in this research. CO2 emissions model explained by several driving factors as a dependent variable In contrast, the additional variables (extended) are foreign direct investment and institutional quality. The data used are the annual time series in Indonesia from 1971 to 2018. This research was investigated using the method of ARDL (Autoregressive Distribution Lag). In the short term, several variables, such as CO2 emission, Affluence, Technology and Institutional Quality, have a positive effect on decreasing environmental quality. In the only variables that have a positive long-term effect is energy structure, are based on the results of the long-term ARDL estimation method in Indonesia.